1987
DOI: 10.1051/jphyscol:1987168
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsometric Study of the Ice Surface Structure Just Below the Melting Point

Abstract: de transition (Q.L.L.) h la surface dlun cristal de glace h tdrature juste en-dessous du point de fusion (O°C) ont 6th mesurds h 116quilibre en utilisant une m6thode d'ellipscnn6trie in-situ. Les couches de transition ont dtd-observ6es h des tdratures sdrieures h -2 et -4OC pour les faces f 0001fet ~1 0 1 0~ respectivement et n1 = 1,330 pour les deux faces. Cette valeur est tres proche de celle de l'eau en volume h 0°C. ~ssoci6 h des observations sur les formes des cristaux de glace prbs du point de fusion, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…There is strong experimental evidence of a liquidlike layer on ice/vapor and ice/solid interfaces. Such a layer was found in NMR experiments by Kvlividze et al and Mizuno and Hanafuza, using optical ellipsometry by Furukawa et al., , in glancing-angle X-ray scattering by Kouchi et al and Dosch et al and using scanning force microscopy by Nickolayev and Petrenko and by Petrenko . In the presence of such a liquidlike layer a part of the screening charge is localized inside the liquid (or quasi-liquid) layer.…”
Section: Other Mechanisms and Approximationsmentioning
confidence: 87%
“…There is strong experimental evidence of a liquidlike layer on ice/vapor and ice/solid interfaces. Such a layer was found in NMR experiments by Kvlividze et al and Mizuno and Hanafuza, using optical ellipsometry by Furukawa et al., , in glancing-angle X-ray scattering by Kouchi et al and Dosch et al and using scanning force microscopy by Nickolayev and Petrenko and by Petrenko . In the presence of such a liquidlike layer a part of the screening charge is localized inside the liquid (or quasi-liquid) layer.…”
Section: Other Mechanisms and Approximationsmentioning
confidence: 87%
“…One manifestation of this perturbation is the "quasi-liquid" layer on ice that is revealed by many experimental techniques. 1,[34][35][36][37][38][39][40] Other theoretical simulations 41 and surface-sensitive probes 42 observed a very dynamic surface on the (0001) basal plane of hexagonal ice. The larger diffusion coefficients measured in the ultrathin ∼300 Å ice multilayers on Ru(001) may be another indication of a more "fluid-like" layer that enhances diffusion in the near surface region.…”
Section: Discussionmentioning
confidence: 99%
“…A sandwich experiment was devised to demonstrate that the H 2 18 O bulk diffusion measurements were not influenced by a possible liquid-like H 2 O layer on the ice surface. 8,[14][15][16][17][18][19][20] This highly fluid layer is monitored at temperatures near the ice melting point, and some experimental results suggest that this layer may persist at temperatures as low as 113 K. 16 In this experiment, a layer of isotopicallylabeled H 2 18 O was sandwiched between two H 2 16 O multilayers, as represented pictorially in Figure 11a. A 28 BL H 2 16 O multilayer was initially grown at 160 K. Subsequently, 1 BL of H 2 18 O was deposited on top of the 28 BL H 2 16 O multilayer at 130 K. An additional 58 BL H 2 16 O multilayer was then condensed on top of the H 2 18 O bilayer at 130 K to create the sandwich.…”
Section: A Surface Diffusionmentioning
confidence: 99%
“…8,10 The "liquid-like" H 2 O layer is also inferred from ice particle sintering and characterized by a variety of experimental techniques. 8,[14][15][16][17][18][19][20] This highly fluid surface layer is clearly observed at temperatures between 243 and 273 K and is associated with rapid H 2 O surface diffusion. In addition, previous investigations have observed that the formation of microporous or crystalline ice may depend largely on the surface diffusion rate.…”
Section: Introductionmentioning
confidence: 99%